Mitochondrial degeneration precedes the development of muscle atrophy in progression of cancer cachexia in tumour‐bearing mice. Issue 6 (28th August 2017) - Brown, Jacob L.; Rosa‐Caldwell, Megan E.; Lee, David E.; Blackwell, Thomas A.; Brown, Lemuel A.; Perry, Richard A.; Haynie, Wesley S.; Hardee, Justin P.; Carson, James A.; Wiggs, Michael P.; Washington, Tyrone A.; Greene, Nicholas P.
Abstract: Background: Cancer cachexia is largely irreversible, at least via nutritional means, and responsible for 20–40% of cancer‐related deaths. Therefore, preventive measures are of primary importance; however, little is known about muscle perturbations prior to onset of cachexia. Cancer cachexia is associated with mitochondrial degeneration; yet, it remains to be determined if mitochondrial degeneration precedes muscle wasting in cancer cachexia. Therefore, our purpose was to determine if mitochondrial degeneration precedes cancer‐induced muscle wasting in tumour‐bearing mice. Methods: First, weight‐stable (MinStable) and cachectic (MinCC) Apc Min/+ mice were compared with C57Bl6/J controls for mRNA contents of mitochondrial quality regulators in quadriceps muscle. Next, Lewis lung carcinoma (LLC) cells or PBS (control) were injected into the hind flank of C57Bl6/J mice at 8 week age, and tumour allowed to develop for 1, 2, 3, or 4 weeks to examine time course of cachectic development. Succinate dehydrogenase stain was used to measure oxidative phenotype in tibialis anterior muscle. Mitochondrial quality and function were assessed using the reporter MitoTimer by transfection to flexor digitorum brevis and mitochondrial function/ROS emission in permeabilized adult myofibres from plantaris. RT‐qPCR and immunoblot measured the expression of mitochondrial quality control and antioxidant proteins. Data were analysed by one‐way ANOVA with Student–Newman–Kuels post hoc test. Results: MinStable mice displayed ~50% lower Pgc‐1α, Pparα, and Mfn2 compared with C57Bl6/J controls, whereas MinCC exhibited 10‐fold greater Bnip3 content compared with C57Bl6/J controls. In LLC, cachectic muscle loss was evident only at 4 weeks post‐tumour implantation. Oxidative capacity and mitochondrial content decreased by ~40% 4 weeks post‐tumour implantation. Mitochondrial function decreased by ~25% by 3 weeks after tumour implantation. Mitochondrial degeneration was evident by 2 week LLC compared with PBS control, indicated by MitoTimer red/green ratio and number of pure red puncta. Mitochondrial ROS production was elevated by ~50 to ~100% when compared with PBS at 1–3 weeks post‐tumour implantation. Mitochondrial quality control was dysregulated throughout the progression of cancer cachexia in tumour‐bearing mice. In contrast, antioxidant proteins were not altered in cachectic muscle wasting. Conclusions: Functional mitochondrial degeneration is evident in LLC tumour‐bearing mice prior to muscle atrophy. Contents of mitochondrial quality regulators across Apc Min/+ and LLC mice suggest impaired mitochondrial quality control as a commonality among pre‐clinical models of cancer cachexia. Our data provide novel evidence for impaired mitochondrial health prior to cachectic muscle loss and provide a potential therapeutic target to prevent cancer cachexia.